Specific meningoencephalitis in patients with transplanted kidney - Tabakovic, Mithat; Trnacevic, Senaid; Taletovic, Maida Dugonjic (Journal of Clinical Nephrology, 2020)
We described a case of specific (tuberculous) encephalitis in a patient after kidney transplantation. Immunosuppressive therapy, continuously required in post-tranplant period, may cause various complications, such as infections. Specific meningoencephalitis is an infection that is rarely diagnosed and more common in immunocompromised patients. Case report: A 30-year-old man had kidney transplantation (kidney donor was his father). He previously was two years on chronic hemodialysis treatment because of end-stagerenal disease based on diabetic nephropathy. He has diabetes type 1. The early post-transplant period duly passed with satisfactory clinical and laboratory parameters of renal function. Two months after transplantation, he presented with febrile condition, signs of septicemia and dehydration with significant neurological deficit and expressed meningeal signs. In cerebrospinal fluid we found lymphocytosis, elevated proteins and positive micobacterium tuberculosis antibodies (Hexagon method) and we suspected to specific etiology of meningitis. Performed computed tomography (CT) scan of the brain with contrast confirmed the expected finding. Due to the poor prognosis of infections of the central nervous system (CNS) in immunocompromised patients, only prompt diagnosis can improve survival in this group of patients. The therapeutic protocol after kidney transplantation include the prophylactic use of antituberculous drug (Isoniazid 300 mg) during the 9 months.